Research Implementation of Special Detection Elementary School Service For Children with Special Needs in Banjarmasin - Suharsiwi, Suharsiwi; Halimatussa'diah, Halimatussa'diah; Fathony, Muhammad Hafiz; Rahmah, Siti; Noor, Pajrian (Department of Special Education, 2024)
In order to shape the abilities and character of children with special needs, it is essential to provide early detection services in public elementary schools. This study, conducted in Banjarmasin, Kalimantan, examined six inclusive elementary schools with 102 children with special needs and 82 special assistant teachers. Using a descriptive qualitative approach with additional quantitative data collection through observations, interviews, and documentation, the study found that some public schools have implemented detection services for children with special needs. Special assistant teachers and coordinators were provided to supervise and support the activities of these children at school. The study concluded that detecting and providing services for children with special needs at an early stage is crucial as elementary school is the foundation for personality development. This is in line with the universal values and religious perspectives that every child has the right to equal education